PENGARUH TINGKAT KESEHATAN BANK TERHADAP HARGA SAHAM PERBANKAN UMUM KONVENSIONAL TERDAFTAR DI BEI 2014-2018 - Bella Salsabilla; Irni Yunita (Jurnal Manajemen Bisnis Krisnadwipayana, 2020)
This research purpose is to analyze the impact of bank soundness on stock price both simultaneously and partially. This research conducted on several indicators which represented by each ratio. There are Good Corporate Governance (GCG), risk profile represented by Non Performing Loan (NPL), capital represented by Capital Adequacy Ratio (CAR), and earning represented by Return on Asset (ROA). The population was conventional banking companies listed on Indonesia Stock Exchange during 2014-2018. Sampling method used in this research was purposive sampling and obtained 32 banking companies as a sample. This research using quantitative method. Analysis technique used in this reseach was panel data regression. The result shows that simultaneously NPL, ROA, CAR have insignificant effect on stock price. However, partially there was a significant effect between GCG and stock price. While the others variable have insignificant effect on stock price.